Keep your eye on the metaphor: The framing of the Common Core on Twitter - Supovitz, Jonathan; Reinkordt, Elisabeth (Education Policy Analysis Archives, 2017)
Issue framing is a powerful way for advocates to appeal to the value systems of constituency groups to evoke their support. Using a conceptual framework that focused on radial frames, metaphors, and lexical markers, we examined the linguistic choices that Common Core opponents used on Twitter to activate five central metaphors that reinforced the overall frame of the standards as a threat to children and appealed to the value systems of a diverse set of constituencies. In our research, we identified five frames: the Government Frame, which presented the Common Core as an oppressive government intrusion into the lives of citizens and appealed to limited-government conservatives; the Propaganda Frame, which depicted the standards as a means of brainwashing children, and in doing so, hearkened back to the cold war era when social conservatives positioned themselves as defenders of the national ethic; the War Frame, which portrayed the standards as a front in the nation’s culture wars and appealed to social and religious conservatives to protect traditional cultural values; the Business Frame, which rendered the standards as an opportunity for corporations to profit from public education and appealed to liberal opponents of business interests exploiting a social good; and the Experiment Frame, which used the metaphor of the standards as an experiment on children and appealed to the principle of care that is highly valued amongst social liberals. Collectively, these frames, and the metaphors and the language that triggered them, appealed to the value systems of both conservatives and liberals, and contributed to the broad coalition from both within and outside of education, which was aligned in opposition to the standards.